An Overview about Research on 3D Visualization Technology of Geographic Information Based on Computer Software Development. Issue 3 (October 2020) - Deng, Xinjie; Jiang, Shuhui
Abstract: Geographic Information System (GIS) is an important system of three-dimensional (3D) real-time interactive visualization platform. 3D visualization technology is to display the information to be expressed by a visual effect. The introduction of 3D visualization technology into GIS is a reform of the form of information expression, which can solve the limitation of using graphic symbols to express the 3D space world on a 2D plane. However, most of the visualizations in GIS focus on the 3D terrain visualization based on the surface model, which does not involve the volume visualization of spatial volume data. An overview about visualization technology for geographic information based on computer software is given here, to encourage further development.